The Mesolithic-Neolithic transition through the Iberian shell middens: a review of current evidence and interpretations - Nukushina, Diana (2018)
Shell middens have been crucial to the discussion about the Mesolithic/Neolithic transition in the Iberian Peninsula from the earliest researches, as in other regions of the Atlantic Europe. Commonly associated to Mesolithic hunter-gatherer groups, shell middens have been subject of extensive research in recent years, stressing their potential as relevant sources ofinformation about these populations. On the other hand, a global decline of shell middens at the beginning of the Neolithic has been widely observed and attributed to changes in settlement and subsistence strategies. However, several cases in the Iberian Peninsula show that the available archaeological data are still limited to firmly support this view. Therefore, it is imperative to critically review the role of these archaeological sites within this historical discussion.